Elektronik Komik Ekosistem (E-Mikosis) Bermuatan Kearifan Lokal Untuk Meningkatkan Kecerdasan Spasial IPA - Achda Subchiya Hanum (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The aim of this study was to analyze the electronic comic ecosystems’ effectiveness (E-Mikosis) to increase students’ science spatial intelligence in fifth grade. E-Mikosis was developed through research and development (R D) with the ADDIE stages. The development consisted of needs analysis, design, product development and validation, implementation, and evaluation. The research was conduted descriptive type of experiment. The product trial carried out was a small-scale trial with a one-shot case study design. The subjects of this study were 6 students in grade fifth of SD 5 Karangebener. The data collection technique in this research was test. The instrument used was in the form of five essay questions based on sciences’ spatial intelligence indicators. The data analysis in this research used quantitative data analysis of descriptive type. The descriptive T-test (One sample t-test) was used to analyze the research data. The result of the descriptive T-test analysis showed the value of Sig. (2-tailed) was 0.031 0.05, then H0 was rejected. The coparison of thit=2.963 ttab=2.015, it mean that thit ttab (H0 was rejected). The analysis concluded that H0 was rejected and Ha was accepted, meaning that the average scores of students’ science spatial intelligence test was ³ 75.